2009
DOI: 10.3354/meps07814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disturbance on marginal populations: human trampling on Ascophyllum nodosum assemblages at its southern distribution limit

Abstract: The negative effects of disturbances on the long-term persistence of populations may be more severe in marginal populations, i.e. those occurring at the boundaries of geographical and ecological distribution ranges. Human trampling is an important source of anthropogenic disturbance for intertidal assemblages. Effects of human trampling on intertidal rocky shore assemblages dominated by Ascophyllum nodosum (L.) Le Jol. at its southern distributional limit in Europe were tested experimentally. Four different in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…trampling) disturbances, which can damage the existing bioconstructions and reduce the density of new recruits (Dubois et al 2002(Dubois et al , 2006. On the studied shore, mechanical impacts from waves and trampling have clear seasonal patterns related to the occurrence of extreme storms, mostly in winter (Dias et al 2002) and human frequentation of the shore, which is particularly intense in summer (Araújo et al 2009). As extreme waves could directly cause seasonal differences in the abundance of S. alveolata that are opposite to the present patterns and trampling might drastically affect intertidal assemblages on emergent rock rather than in rock pools, both mechanisms are unlikely to provide convincing explanations to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…trampling) disturbances, which can damage the existing bioconstructions and reduce the density of new recruits (Dubois et al 2002(Dubois et al , 2006. On the studied shore, mechanical impacts from waves and trampling have clear seasonal patterns related to the occurrence of extreme storms, mostly in winter (Dias et al 2002) and human frequentation of the shore, which is particularly intense in summer (Araújo et al 2009). As extreme waves could directly cause seasonal differences in the abundance of S. alveolata that are opposite to the present patterns and trampling might drastically affect intertidal assemblages on emergent rock rather than in rock pools, both mechanisms are unlikely to provide convincing explanations to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, harvesting and trampling could be important processes acting at this spatial scale. Many of the studied locations such as Foz, Aguda, Amorosa and Viana are exposed to an intense seasonal trampling due to recreational activities in summer, and Araújo et al (2009) found negative effects of trampling on macroalgal assemblages. Harvesting of invertebrates such as sea urchins is noticeable in many locations such as Viana or Belinho (personal observation).…”
Section: Discussionmentioning
confidence: 99%
“…A previous experimental study on the Portuguese population of Ascophyllum nodosum showed that high intensities of human trampling can negatively affect the mean abundance of this species, the cooccurring fucoid Fucus vesiculosus and understorey species, while enhancing the cover of ephemeral green algae (Araújo et al 2009). However, how changes in the intensity of disturbance affect spatial and temporal patterns of the same population and associated organisms has never been experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Intense trampling associated with such activities can drastically affect patterns of distribution, abundance and diversity of macroalgal assemblages on rocky shores (Keough & Quinn 1998, Araújo et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation